(untitled) (Research, Society and Development, 2022)
The use of multi-criteria decision-making methods aims to optimize decision-making process from sets of criteria and characteristics that are sometimes disregarded in other ways of selecting priorities for the decision task. Accordingly, decisions that require technical criteria for the implementation of public services can benefit from the use of, for example, the Analytic Hierarchy Process (AHP). The purpose of this paper is to demonstrate how and based on what objective and subjective criteria the AHP can be used to decide where to implement the Casa da Mulher Brasileira, one of the main facilities to assist women victims of violence, in the Metropolitan Region of Belém, capital of Pará, Amazon. Using as criteria Cases of Violence, Female Population in each of the five municipalities and Accessibility to them, it was verified that the capital, Belém do Pará, is the most appropriate municipality to receive the public facility within the region considered.